Effect of non-surgical periodontal treatment on HbA1c levels in non-diabetic patients with chronic periodontitis in an Iranian population - Fereshteh Naseralavi; masumeh nikkhah; Nastaran Etemadi; Ashkan Salari (Tabriz University of Medical Sciences, 2019)
Background. Evidence is limited on the effect of periodontal treatment on improving HbA1c levels in non-diabetic patients with chronic periodontitis. This study aimed to compare HbA1c levels in non-diabetic patients without periodontitis and nondiabetic patients with chronic periodontitis at baseline and to evaluate the effect of non-surgical periodontal treatment on glycemic control in non-diabetic chronic periodontitis patients. Methods. In this interventional study, 30 non-diabetics, aged 35‒65 years, were selected and divided into two groups (n=15). Group A consisted of non-diabetics without periodontitis, and group B consisted of non-diabetics with mild to moderate chronic periodontitis. For all the subjects, periodontal parameters, including plaque index, gingival index, periodontal pocket depth, and clinical attachment loss, and laboratory parameters of FBS and HbA1c were measured and recorded. Independentsamples t-test was used to compare periodontal and laboratory parameters between the two groups; paired-samples t-test was used for intra-group comparisons. Results. HbA1c level in group B (5.4±0.42%) was significantly higher than that in group A (5.04±0.43%) (P=0.03) at baseline. Three months after treatment, improvements were achieved in all the periodontal parameters in group B, with a significant decrease in HbA1c levels (P=0.006). Conclusion. Non-surgical periodontal treatment resulted in a significant decrease in HbA1c levels in non-diabetic patients with chronic periodontitis. Although these levels did not reach the level of non-diabetic patients without periodontitis, it could be concluded that an improvement in the periodontal condition might lead to near-normal glycemic levels.